Preliminary Phytochemical Screening and Anthelmintic Activity of Chloroxylon swietenia Root Extract - Ranjit Kumar Harwansh; Surendra Kumar Pareta; Kartik Chandra Patra; Md. Akhlaquer Rahman (International Journal of Phytomedicine, 2010)
The preliminary phytochemical investigation was carried out on the crude extracts of the roots of Chloroxylon swietenia. The crude extracts were investigated for their anthelmintic activity against Indian earthworms (Pheretima posthuma). Three concentrations (25, 50 and 100 mg/mL) of each extract were performed in activity, which involved the evaluation of paralysis and death period of the worm. Chloroform and methanol extracts exhibited significant anthelmintic activity at highest concentration of 100 mg/mL. Piperzine citrate was selected as standard compound and Di-methyl formamide as control. The anthelmintic activity of Chloroform and methanol of roots of Chloroxylon swietenia has therefore been evaluated for the first time.